"An Injury like Any Other": Counter Story, Mental Health Discourse, and Liz Cambage. Issue 5 (20th October 2022) - Lavelle, Katherine
Abstract: Recently, more elite athletes have publicly disclosed their mental health experiences in a variety of media texts. In 2019, Australian WNBA (Women's National Basketball Association) player Liz Cambage, who self-identifies as biracial, revealed her experiences with depression, anxiety, substance abuse and panic attacks that have interrupted her professional career multiple times. For communication studies scholars, Cambage's discourse, we must examine it because Black women are frequently encouraged to compartmentalize their emotions and mental health stressors instead of expressing them. It is critical to examine this discourse for WNBA players who spend most of their time away from home as they participate in multiple professional leagues every year. Using Critical Race Theory, specifically the concept of a counter story, this essay argues that Cambage's mediated mental health disclosures function as resistance to stereotypes about Black women and mental health.